1998
DOI: 10.1255/ejms.227
|View full text |Cite
|
Sign up to set email alerts
|

Energy partitioning in collisions of slow polyatomic ions with surfaces: ethanol molecular ions on stainless steel surfaces

Abstract: Mass spectra and translational and angular distributions of product ions formed in interactions of 13-33 eV ethanol molecular ions (C 2 H 6 O +• ), as well as C 2 H 7 O + and C 2 H 5 O + ions, with a stainless steel surface were investigated to determine the partitioning of energy in the collisions with the surface. Distribution functions were derived from the data for the energy fractions going into internal excitation of the projectile, product translational energy and that absorbed by the surface. The peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
84
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 10 publications
10
84
0
Order By: Relevance
“…Such an effect is not seen experimentally in collisions with a surface consisting of large organic molecules or self-assembled monolayers, [40 -42] and computationally in collisions with a self assembled monolayer (SAM) [38]. Herman and coworkers [40] studied collisions of ethanol molecular ions, C 2 H 6 O ϩ• , with stainless-steel surfaces covered by a multilayer of hydrogen-containing substances, usually identified as (pump oil) hydrocarbons, and found that the probability of energy-transfer to the ion's internal degrees of freedom, ⌬E int , is independent of i in the range of 40°to 80°. They found the same result in collisions of the same ion, C 2 H 6 O ϩ• , with perfluoro (F-SAM), hydrogenated (H-SAM), and -COOH terminated (HOOC-SAM) alkylthiol selfassembled monolayer surfaces for collisions with i in the same range [41,42].…”
Section: Comparison With Previous Experimentsmentioning
confidence: 99%
“…Such an effect is not seen experimentally in collisions with a surface consisting of large organic molecules or self-assembled monolayers, [40 -42] and computationally in collisions with a self assembled monolayer (SAM) [38]. Herman and coworkers [40] studied collisions of ethanol molecular ions, C 2 H 6 O ϩ• , with stainless-steel surfaces covered by a multilayer of hydrogen-containing substances, usually identified as (pump oil) hydrocarbons, and found that the probability of energy-transfer to the ion's internal degrees of freedom, ⌬E int , is independent of i in the range of 40°to 80°. They found the same result in collisions of the same ion, C 2 H 6 O ϩ• , with perfluoro (F-SAM), hydrogenated (H-SAM), and -COOH terminated (HOOC-SAM) alkylthiol selfassembled monolayer surfaces for collisions with i in the same range [41,42].…”
Section: Comparison With Previous Experimentsmentioning
confidence: 99%
“…The agreement between experimental and calculated abundances of ions for the direct dissociation CERMS curves was good over the range of incident energies 11-30 eV, as shown in comparison with the experimental (SS and DO surfaces) and calculated spectra in Table 3. Thus, the fraction of translational energy converted into internal energy, derived for collisions of C 2 D 4 ϩ with the above studied different surfaces at room temperature, is 10% of the incident translational energy, somewhat larger than the often quoted value [5,16,20,29] of about 6%. However, the present case is more complicated because the final internal energy of the surface-excited projectile ion, P(E' int ), is composed of two components of comparable magnitude, the initial internal energy of the projectile ion, P(E int ) and the component from net conversion of translational-to internal energy in the surface collision, P(E' conv ).…”
Section: Estimation Of the Internal Energy Of The Surface-excited Promentioning
confidence: 54%
“…In our estimation of the internal energy of C 2 D 4 ϩ excited in surface collisions, we used the CERMS curves for the direct dissociative processes (Figure 3) and followed the procedure used in our previous papers [5, ϩ as a function of the incident energy for different surfaces. 16,18,29]. This procedure is based on using different forms of energy-transfer distributions together with the breakdown pattern of the incident ion in question, trying to find the best fit with the relative abundance of the product ions in the mass spectrum of the surfaceexcited ions at different incident energies.…”
Section: Estimation Of the Internal Energy Of The Surface-excited Promentioning
confidence: 99%
See 2 more Smart Citations